The Potential of Hydrothermally Pretreated Industrial Barks From E. globulus as a Feedstock for Pulp Production. (1st November 2016) - Neiva, Duarte M.; Gominho, Jorge; Fernandes, Luís; Lourenço, Ana; Chemetova, Catarina; Simões, Rogério M. S.; Pereira, Helena
Abstract : This study focused on the use of industrial eucalyptus globulus bark as an alternative fiber source for bleached pulp and paper production. Bark has high extractives and ash contents (7.7% and 3.5%, respectively) but a mild hydrothermal pretreatment was tested, decreasing its values to 2.8% and 2.4%, respectively. Untreated and pretreated bark were kraft pulped at 15% and 20% (as Na2 O) active alkali conditions. The pretreatment improved delignification when using low active alkali; kappa number 25.4 vs 17.5, and shives 3.1% vs 0%, respectively, with untreated and pretreated bark. The pretreatment resulted in a lower chemical demand to obtain pulps with similar yield and kappa number. It was possible to produce bleached pulps with good handsheet optical, physical, and mechanical properties with slightly lower values than those of industrial eucalypt wood pulps; e.g., brightness > 85% vs 87%, tear index > 4.2 vs 5.6 mn.m 2 .g −1, tensile index > 62 vs 69 n.m.g −1 for bark and wood pulps, respectively.